BITCOIN DALAM SISTEM HUKUM INDONESIA (Lex Jurnalica, 2021)
This study aims to determine and understand whether bitcoin can be categorized as a means of payment exchange in Indonesia and how the legality of positive Indonesian law in regulating bitcoin issues. The research method used is a normative research method. The approach method used in this research is the statutory approach and the conceptual approach. Bitcoin clearly does not meet the requirements of money in theory and the Currency Act only recognizes the rupiah as a legal medium of exchange, and under the Currency Act, bitcoin cannot be said to be money. Apart from not being able to be said to be bitcoin money, it can also not be said to be electronic money. Law No. 7 of 2011 concerning Currency, it is stated that Indonesia only recognizes Rupiah as a legal medium of exchange for Bitcoin and Other Virtual Currency” which basically states that bitcoin and other virtual currencies are not legal tender in Indonesia, so the risk associated with the use of bitcoin is borne by the owner. or the bitcoin user concerned.This study aims to determine and understand whether bitcoin can be categorized as a means of payment exchange in Indonesia and how the legality of positive Indonesian law in regulating bitcoin issues. The research method used is a normative research method. The approach method used in this research is the statutory approach and the conceptual approach. Bitcoin clearly does not meet the requirements of money in theory and the Currency Act only recognizes the rupiah as a legal medium of exchange, and under the Currency Act, bitcoin cannot be said to be money. Apart from not being able to be said to be bitcoin money, it can also not be said to be electronic money. Law No. 7 of 2011 concerning Currency, it is stated that Indonesia only recognizes Rupiah as a legal medium of exchange for Bitcoin and Other Virtual Currency” which basically states that bitcoin and other virtual currencies are not legal tender in Indonesia, so the risk associated with the use of bitcoin is borne by the owner. or the bitcoin user concerned.